مهارات ما وراء المعرفة وعلاقتها بفعالية الذات لدى تلاميذ المرحلة الإعداداية - نورهان ياسر فهمى حمزة حمزة; هشام إبراهيم النرش النرش; إبراهيم محمد المغازي المغازي (Faculty of Education - Port Said University, 2020)
يهدف البحث الحالى إلى التعرف على مهارات ما وراء المعرفة وعلاقتها بفعالية الذات لدى تلاميذ المرحلة الإعدادية . تکونت العينة النهائية للدراسة من (174) تلميذاً وتلميذة من تلاميذ المرحلة الإعدادية بمدراس محافظة بورسعيد ، وتم استخدام مقياس مهارات ما وراء المعرفة (إعداد الباحثة) ، مقياس فعالية الذات إعداد (Tipton & Worthington,1984) ترجمة محمد السيد عبد الرحمن (1990)، وتوصلت نتائج الدراسة إلى وجود علاقات ارتباطية موجبة دالة إحصائياً عند مستوى 0.01 بين مهارات ما وراء المعرفة (الوعى - التخطيط - المراقبة والتحکم - المراجعة والتقويم) وفعالية الذات لدى تلاميذ المرحلة الإعدادية. The study aims to recognize the relation between Metacognitive-Skills and Self-Efficacy among preparatory stage students . The final sample of the study consists of (174) pupils from preparatory stage students in Port Said Governorate schools . (88 males / 86 females) from preparatory stage student in Port Said city's schools . The metacognitive-skills scale (researcher preparation) and self-efficacy scale (Tipton & Worthington, 1984) were used . The results of the study found that there are positive correlations statistically significant at the level of 0.01 between Metacognitive-Skills (awareness - planning- control and control - .review and evaluation) and self - efficacy in the preparatory stage students